Recent developments in the Japanese ivory trade and the implementation of CITES in Japan - Tom Milliken (Pachyderm)
Notes that the ivory imports into Japan were not so easily cut off as had been hoped in an article in the previous issue, Pachyderm 4 p19, but the situation led to the development of the Zoogei Bukai (Ivory Importers Group) which brough together 25 ivory importers within the Japan General Merchanise Importers' Association. An Administrative Guidance to importers has been issued and holds promise for 1985 the abuse of last year cannot be changed. Japan's ivory imports for 1984 were 473 tons second only to the record set in year of 1983 of 475 tons.